Evolution of human-land relations from 7100aB.P.-3700aB.P. in the Southern Jiangsu region - Wang, Sheng (Technium Social Sciences Journal, 2025)
The article explores the evolution of human-land relations, especially the process of land-use conversion, in the Southern Jiangsu region during the 7100aB.P.-3700aB.P. time period from the spatial cultural distribution of archaeology, the spatial morphology of settlement sites and the Holocene environmental changes.The results show that the archaeological cultures of the Southern Jiangsu region interacted with environmental changes during this period, and that in the transitional phase of the 7100aB.P.-3700aB.P. Huaxia culture, the degree of land use of ancient humans deepened, and human response to nature gradually changed to proactive measures.